Penegakan Hukum Terhadap Tindak Pidana Perjudian Online dari Perspektif Hukum Informasi dan Transaksi Elektronik (Studi Kasus Kota Kupang) - Akbar Nur Wijaya Asra; Bhisa V. Wilhelmus; Deddy R. Ch. Manafe (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
One of the negative impacts of the internet is online gambling, which previously people only played gambling games in the usual way. Gambling has been around on this earth for thousands of years and is the oldest game in the world. In essence, gambling is behavior that violates religious, ethical, moral and legal norms and endangers the livelihood of the community and the life of the community, nation, and state. This research was carried out in Kupang City, precisely at the Kupang City Resort Police. This research is an empirical legal research, which is carried out by looking at the reality that exists in field practice. This approach is also known as a sociological approach that is carried out directly in the field. The data were analyzed in a descriptive-qualitative manner. Based on the results of the research that has been carried out, it is obtained that: (1) Law enforcement efforts against perpetrators of online gambling crimes, including: (a) The application of criminal sanctions for perpetrators of online gambling crimes in accordance with applicable laws and regulations. (b) Strict action to take legal action against the perpetrators of online gambling crimes. (2) Factors that are obstacles in the process of handling online gambling crimes, include: (a) Obstacles to law enforcement, (b) Lack of awareness and concern from the public, (c) Server factors located outside the Kupang City area, (d) Inadequate facilities and infrastructure, (e) Difficulty in collecting evidence. The author's suggestion is to tackle online gambling crimes, not only by relying on the role of the Police, but also the need for participation from the community. The public should not be closed and more open in providing information and reports to the Police regarding gambling crimes that occur around the area where they live.